An updated catalogue of the Collembola (Hexapoda) from Colombia and a perspective for unexplored richness - Cipola, Nikolas Gioia (Zootaxa, 2023)
An updated catalog of Collembola nominal species recorded in Colombia is herein provided, including two new records for the country: Entomobrya linda Soto-Adames, 2002 and Folsomides centralis (Denis, 1931), both found in Reserva Natural Mesenia – Paramillo (Antioquia Department). The data were obtained from the original descriptions, as well as secondary records surveyed until December 2022. I considered localities whose studies contained identification at generic level, but disregarded those who only contained records at family level. For each species, its type locality and general distribution were provided, in addition to the site of record in Colombia, which were plotted on a map. I also present the cumulative number of nominal species recorded and described from Colombia from 1929 to 2022. Colombia has now 38 nominal species (20 endemic) in 21 genera (one endemic, plus 19 without nominal species) and 16 families of Collembola distributed in 22 sites of the 11 departments and five regions. Of this total of families, Bourletiellidae, Collophoridae, Hypogastruridae and Sminthuridae only has generic records, no nominal species. Based on these data, an estimate of the species richness was made suggesting that at the current rate of species records, to recognize 231 to 250 more species (6–7 species every 10 years), it will take about 300 years, and even so this time will not be sufficient to unveil the real fauna of Collembola of the country. For that reason, these results suggest that the Collembola fauna from Colombia is still underestimated in relation to other countries from South America.